The Imperative of Zakat on Financial Instruments in a Globalized Economy - Maspul, Kurniawan; Mubarak, Islahuddin (Journal of Waqf and Islamic Economic Philanthropy, 2025)
Amidst a $109 trillion global equity market and widening wealth chasms, this study repositions Zakat—Islam’s divine wealth tax—as a radical antidote to neoliberal excess. Synthesizing juristic rigor with empirical analysis, it asserts stocks and asset-backed sukuk as Zakatable under Urud al-Tijarah, contingent on trade intent and Shariah compliance. Indonesia’s BAZNAS emerges as paradigmatic, diverting 12% of $700M annual Zakat from equities to uplift 15,000 families, while Malaysia’s automated systems and Saudi profit-levies reveal scalable blueprints. Yet $1 trillion in uncollected Zakat persists, shackled by bond-based riba, regulatory disarray, and valuation ambiguities. The work champions blockchain traceability, AI-driven compliance, and harmonized global frameworks to unlock Zakat’s latent power. By fusing prophetic ethics with fintech innovation, this research reengineers capitalism’s DNA—transforming speculative markets into conduits of sacred equity, where prosperity is not hoarded but flowed, as Imam Al-Ghazali envisioned, to every corner of our parched world.